Unmet information needs and impact of cancer in (long‐term) thyroid cancer survivors: results of the PROFILES registry. Issue 8 (11th March 2014) - Husson, O.; Mols, F.; Oranje, W. A.; Haak, H. R.; Nieuwlaat, W. A.; Netea‐Maier, R. T.; Smit, J. W. A.; van de Poll‐Franse, L. V.
Abstract Objective The objective of this study was to provide insight into the following: (a) the perceived level of, satisfaction with, and helpfulness of received information and unmet information needs among thyroid cancer (TC) survivors and (b) the relation between unmet information needs and impact of cancer (IOC). Methods All patients diagnosed with TC between 1990 and 2008, as registered in the Eindhoven Cancer Registry, received a survey on information provision (European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Information module) and IOC. Results Thyroid cancer survivors (n = 306; response rate = 86%) indicated to receive no or only a little information about different aspects of their disease (27–86%), medical tests (20–27%), treatment (21–90%), and aftercare (86–91%). Almost half of the survivors (47%) were not at all or a little satisfied with the amount of information received; 31% found the received information not or a little helpful; a third of the patients (34%) indicated that they wanted to receive more information (defined as unmet needs). TC survivors with unmet informational needs scored significantly higher on both the positive (mean 3.2 vs. 2.9) and negative IOC scale (mean 2.5 vs. 2.2) compared with survivors without unmet needs (p < 0.01). In multivariate linear regression analyses, unmet information needs were positively associated with all positive IOC scales except positive self‐evaluation (betas ranging from 0.16 to 0.24; p < 0.05), and all negative IOC scales except for appearance concerns (betas ranging from 0.12 to 0.19; p < 0.05). Conclusion Thyroid cancer survivors experienced several areas of information provision as insufficient, suggesting room for improvement. Unmet information needs among TC survivors are associated with both positive and negative impacts of cancer. Copyright © 2014 John Wiley & Sons, Ltd.